Definition and attributes of the emotional memory images underlying psychophysiological dis-ease - Hudson, Matt; Johnson, Mark I. (Frontiers in Psychology, 2022)
Background: Previously, we proposed a “split-second learning” model to explain how emotional memories could be preventing clients from adapting to the stressors of daily living, thus forming a barrier to learning, health and well-being. We suggested that these emotional memories were mental images stored inside the mind as ‘emotional memory images’ (EMIs). Objective: To elaborate on the nature of these emotional memory images within the context of split-second learning and unlearning and the broader field of psychoanalysis, to initiate a conversation among scholars concerning the path that future healthcare research, practice, and policy should take. Method: A narrative review of the attributes of EMIs utilising relevant and contentious research and/or scholarly publications on the topic, facilitated by observations and approaches used in clinical practice. Results: We propose a refined definition of EMIs as Trauma induced, nonconscious, contiguously formed multimodal mental imagery, which triggers an amnesic, anachronistic, stress response within a split-second. The systematic appraisal of each attribute of an EMI supports the idea that the EMI is distinct from similar entities described in literature enabling further sophistication of our ‘split second learning model of psychophysiological dis-ease. Conclusion: Exploration of the concept of EMIs provides further insight on mechanisms associated with psychophysiological dis-ease and opportunities for therapeutic approaches.